Parabolic trough or linear fresnel solar collectors? An exergy comparison of a solar-assisted sugarcane cogeneration power plant. (March 2021) - López, Juan Camilo; Escobar, Alejandro; Cárdenas, Daniel Alejandro; Restrepo, Álvaro
Abstract: In this paper, two different types of solar thermal collector are compared on an exergy basis in the context of a sugarcane cogeneration power plant in Colombia. The analysis is conducted considering the use of solar energy as a way to preheat the boiler feedwater and thereby reduce the fuel consumption and exergy destruction of the power plant. The energy and exergy analyses of the power plant are conducted under real and steady-state conditions. A parabolic trough collector and a linear Fresnel collector are compared, and their exergy performances are assessed. The comparison is conducted considering both solar fields are sized to preheat the boiler feedwater from 95 °C to 150 °C. The inclusion of the solar thermal collectors reduces the fuel consumption by 1.1% during a typical meteorological year, equivalent to 6400 tons of bagasse per year. Furthermore, the PTC generated 35% more heat per m 2 of aperture area during the year than LFC. A better solar exergy harvesting was achieved for the PTC. However, the results do not show significant differences in terms of exergy destruction and fuel savings between the PTC and the LFC. Highlights: PTC and LFC are compared in terms of energy and exergy. The integration of solar energy into a sugarcane cogeneration cycle is assessed. An hour-by-hour operation is analyzed during a typical meteorological year. Significant differences between PTC and LFC in terms of exergy were not found. PTC generated 35% more heat per m2 than LFC.